2009
DOI: 10.1227/01.neu.0000341872.17024.44
|View full text |Cite
|
Sign up to set email alerts
|

Hyperemia Beneath Evacuated Acute Subdural Hematoma Is Frequent and Prolonged in Patients With an Unfavorable Outcome

Abstract: On average, hyperemic long-lasting rCBF values frequently occur in the cortex located beneath an evacuated SDH and seem to be associated with unfavorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 59 publications
3
15
0
Order By: Relevance
“…(23) describes the time course of global CBF in 522 studies (unpublished data). A similar time course of rCBF has been observed in traumatic contusion by means of intravenous 133 Xenon [79], in traumatic intra-parenchymal hematoma [75] and in the cortex below the evacuated SDH by means of Xe-CT [44]. Although this pattern has been described in pooled patients with TBI it seems to characterize only patients with unfavorable outcome as shown in two studies in which data were dichotomized for favourable and unfavourable outcome [44,76].…”
Section: Time Course Of Cbfsupporting
confidence: 62%
See 2 more Smart Citations
“…(23) describes the time course of global CBF in 522 studies (unpublished data). A similar time course of rCBF has been observed in traumatic contusion by means of intravenous 133 Xenon [79], in traumatic intra-parenchymal hematoma [75] and in the cortex below the evacuated SDH by means of Xe-CT [44]. Although this pattern has been described in pooled patients with TBI it seems to characterize only patients with unfavorable outcome as shown in two studies in which data were dichotomized for favourable and unfavourable outcome [44,76].…”
Section: Time Course Of Cbfsupporting
confidence: 62%
“…Although this pattern has been described in pooled patients with TBI it seems to characterize only patients with unfavorable outcome as shown in two studies in which data were dichotomized for favourable and unfavourable outcome [44,76]. According to these studies, this pattern proved to apply to both global CBF [76] and regional CBF, at least in patients affected by isolated SDH [44].…”
Section: Time Course Of Cbfmentioning
confidence: 96%
See 1 more Smart Citation
“…Prolonged brain retraction may cause severe disturbance in the parenchymal biochemical patterns in the brain underlying an evacuated acute subdural hematoma leading to microthrombosis or vascular wall disintegration [14]. This combined with defective autoregulation and hyperemic long-lasting regional cerebral blood flow values can cause secondary bleeding leading to unfavorable outcome [2,8,10,15,16]. Bleeding has also been reported during the evacuation process [17].…”
Section: Discussionmentioning
confidence: 99%
“…Brainstem CBF measured at the level of the superior colliculus less than 40cc/100g/min has also been highly correlated with poor outcome [55]. A recent study showed that in patients with TBI who have evacuation of an acute subdural hematoma, that there is a persistent hyperemia under the area of evacuation, likely due to the metabolic disturbances described above, and furthermore, that this situation is associated with worse outcomes [56].…”
Section: Xenon/ct In Traumatic Brain Injurymentioning
confidence: 99%